Viral immune evasins impact antigen presentation by allele-specific trapping of MHC I at the peptide-loading complex - Sethumadhavan, Sunesh; Barth, Marie; Spaapen, Robbert M.; Schmidt, Carla; Trowitzsch, Simon; Tampé, Robert (Scientific reports, 2022)
Major histocompatibility complex class I (MHC I) molecules present antigenic peptides to cytotoxic T cells to eliminate infected or cancerous cells. The transporter associated with antigen processing (TAP) shuttles proteasomally generated peptides into the ER for MHC I loading. As central part of the peptide-loading complex (PLC), TAP is targeted by viral factors, which inhibit peptide supply and thereby impact MHC I-mediated immune responses. However, it is still poorly understood how antigen presentation via different MHC I allotypes is affected by TAP inhibition. Here, we show that conditional expression of herpes simplex viral ICP47 suppresses surface presentation of HLA-A and HLA-C, but not of HLA-B, while the human cytomegaloviral US6 reduces surface levels of all MHC I allotypes. This marked difference in HLA-B antigen presentation is echoed by an enrichment of HLA-B allomorphs at US6-arrested PLC in comparison to ICP47-PLC. Although both viral factors prevent TAP-mediated peptide supply, our data imply that MHC I allomorphs favor different conformationally arrested states of the PLC, leading to differential downregulation of MHC I surface presentation. These findings will help understand MHC I biology in general and will even advance the targeted treatment of infections depending on patients’ allotypes.